THE NEED OF INTERPRETATION IN MASS MEDIA DISCOURCE - Ergasheva, Arofat (Innovative Development in Educational Activities, 2023)
The subject of research in this article is the mass media discourse. The purpose of the work is to theoretically interpret the mass media discourse in the context of modern society and practice of media communications. The study of mass media discourse considers the features of the platforms, its production and importance, as well as its representation. The work uses a set of methods: comparative analysis and interpretative analysis. The definition of the mass media discourse allows us to expand the understanding of this category in modern media communications.